2018
DOI: 10.1084/jem.20180230
|View full text |Cite
|
Sign up to set email alerts
|

Activated CARD11 accelerates germinal center kinetics, promoting mTORC1 and terminal differentiation

Abstract: Activating mutations in the adapter protein CARD11 associated with diffuse large B cell lymphomas (DLBCLs) are predicted to arise during germinal center (GC) responses, leading to inappropriate activation of NF-κB signaling. Here, we modeled the B cell-intrinsic impact of the L251P activating mutation in CARD11 (aCARD11) on the GC response. Global B cell aCARD11 expression led to a modest increase in splenic B cells and a severe reduction in B1 B cell numbers, respectively. Following T cell-dependent immunizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
(109 reference statements)
0
13
0
Order By: Relevance
“…DLBCL could also be suggestive when considering pharmacological control of B‐cell proliferation. Findings in a transgenic mouse model demonstrated that the inducible expression of a DLBCL‐mimicking CARD11 mutant led to increased mTORC1 signaling in germinal center B cells 19 . In a clinical setting, the mTOR inhibitor sirolimus was administered to two patients with BENTA and relieved their lymphadenopathy and splenomegaly 9 .…”
Section: Discussionmentioning
confidence: 99%
“…DLBCL could also be suggestive when considering pharmacological control of B‐cell proliferation. Findings in a transgenic mouse model demonstrated that the inducible expression of a DLBCL‐mimicking CARD11 mutant led to increased mTORC1 signaling in germinal center B cells 19 . In a clinical setting, the mTOR inhibitor sirolimus was administered to two patients with BENTA and relieved their lymphadenopathy and splenomegaly 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, it was recently shown that activating mutations in CARD11 (observed in~5% of DLBCL (ref. 5 )), a NF-κB activator protein downstream BCR signaling, increases GC formation and GC B-cell proliferation through enhanced cycling 64 . GC B cells represent the origin of several BCLs including DLBCL (ref.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo EdU labeling for cell cycle analysis was performed as previously described 100 . Briefly, 5-ethynyl-2'-deoxyuridine (EdU, Thermo Fisher) was dissolved in sterile DMSO and 1mg in a volume of 100ul was injected i.p.…”
Section: Cell Cycle Analysis Using In Vivo Edu Labelingmentioning
confidence: 99%